Proteinuria pada Penderita Gagal Ginjal Kronik di Rumah Sakit Martha Friska Multatuli Medan Tahun 2015-2016 - Juliana Ruminta Sijabat; Sartini Sartini; Abdul Karim (Universitas Medan Area, 2019)
This study aims to determine the presence or absence of protein in urine in patients with chronic renal failure. From the results of the study it was found that patients with chronic kidney failure in Martha Friska Multatuli General Hospital Medan from the 80 most patients in positive +++. Many patients with chronic kidney failure are male patients (62.5%) compared to female patients (37.5%) and the results of the examination based on age increase with age, ie at the age of 45 years and above. This type of research is descriptive analytic. Data is taken by recording medical record data of patients with chronic kidney failure based on age, sex and year. The study was conducted from January 2015 to December 2016. The place for conducting the research was conducted at Martha Friska Multatuli General Hospital (RSU) Medan. The study sample was urine samples from all patients with chronic renal failure. It can be concluded that the picture of protein in urine in patients with chronic kidney failure increases every year.